Directly visualizing the sign change of d-wave superconducting gap in Bi2Sr2CaCu2O8+δ by phase-referenced quasiparticle interference - Qiangqiang Gu (Nature Portfolio, 2019)
The superconducting gap structure contains important information to understand the pairing mechanism of unconventional superconductivity. Here, by using a newly established phase-referenced quasiparticle interference technique, the authors visualize the sign change of the d-wave superconducting gap directly in Bi2Sr2CaCu2O8+δ.